Professional nurses’ perspectives of an ideal performance management process - Sibonelo Ndlovu; Neltjie C. van Wyk; Ronell Leech (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: A well-managed performance management process can significantly influence professional nurses’ job satisfaction and improve patient outcomes. Conversely, ineffective management of the process can lead to demotivation of the nursing staff.